Relasi Antara Investor Pariwisata Dengan Masyarakat Lokal Di Desa Pakraman Laplapan Desa Petulu Kecamatan Ubud - Suprapta, I Ketut Agus Gita; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2018)
The research titled is "relationship between tourism investors and lokal communities in Desa Pakraman Laplapan Petulu Village (Case Study Social Conflict)", purpose to understand the relationship undertaken by tourism investors with lokal communities that happened in the Ubud tourist destination. Data were collected through observation, interview and literature study. Infoman taken by purposive, which determine the informan with a certain considerations that are considered able to provide data to the maximum in accordance with the criteria of the research objectives. The collected data were analyzed descriptively qualitative. An important concept in the study include the concept of Typology Relations Styling in 3 Zone which consists of the outer zone, the middle zone and center zone. The results of this study indicate that, Desa Pakraman Laplapan as a region lies in the outer zone. Relationships that lived between tourism investors and lokal communities in Desa Pakraman Laplapan patterned conflictual. This pattern is shown by the regulation provided by the lokal community to tourism investors who are less rational. As for the view of the conflict is a way to snatch for limited resources. And one of them is the economic resource owned by the investor. Styling tourism investor relations with the lokal community in Desa Pakraman Laplapan has been sticking to the surface of the endless conflict. In this case, the farmer must make good relationship with tourism investors because it would help to farmers.   Keywords : Relationship, Investors, Lokal Communities, Conflict